Using 2D simulation applications to motivate students to learn STEAM - Tembo, Tercia Marie Tafadzwa; Lee, Chien Sing * (2017)
In this paper, we discuss the declining interest in STEM subjects of high school students in Malaysia and delve into our ongoing research towards developing a learning activity that will motivate them to pursue learning STEAM. The activity is developed using a combination of Learning by Design pedagogy along with PhET and Algodoo Simulation applications to teach students Physics topics facilitated by a website with gamification features.